2017
DOI: 10.15805/addicta.2017.4.1.0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nursing and Mechanical Engineering Students’ Codependency Levels

Abstract: This study aims to determine and compare nursing students' and mechanical engineering students' codependency levels and the factors that affect codependency. This study is designed as a descriptivecomparative research. Data has been collected using an information form and the Codependency Assessment Tool (CODAT). Higher scores indicate higher levels of codependency. The sample consists of 283 undergraduate students who voluntarily participated in this study. The data has been evaluated in SPSS 11.5 using stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…It was determined that the mean total score in the CODAT of the students who participated in the study was 52.52 ± 13.52, and that in the sub‐dimensions, the highest mean score was in the hidden self sub‐dimension while the lowest mean was in the medical/psychosomatic problems sub‐dimension. In the study by Aktaş Özakgül et al (2017), it was found that the mean codependency scores of the students was moderate (51.89 + 9.93). The fact that the majority of members of the profession are women, professional practices are based on communication, and emotions are at the forefront facilitates the development of codependency, while the fact that it is a profession that requires being sensitive to and caring for someone else's needs is considered to increase the frequency of codependency (Ançel, 2012; Özdemir & Buzlu, 2020).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…It was determined that the mean total score in the CODAT of the students who participated in the study was 52.52 ± 13.52, and that in the sub‐dimensions, the highest mean score was in the hidden self sub‐dimension while the lowest mean was in the medical/psychosomatic problems sub‐dimension. In the study by Aktaş Özakgül et al (2017), it was found that the mean codependency scores of the students was moderate (51.89 + 9.93). The fact that the majority of members of the profession are women, professional practices are based on communication, and emotions are at the forefront facilitates the development of codependency, while the fact that it is a profession that requires being sensitive to and caring for someone else's needs is considered to increase the frequency of codependency (Ançel, 2012; Özdemir & Buzlu, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…This result was considered to be due to the fact that child development is also a profession focused on helping just like nursing. Furthermore, similar results were also obtained in a study comparing the codependency levels of nursing and mechanical engineering students (Aktaş Özakgül et al, 2017). An individual who exhibits codependent personality traits may especially choose professions that are suitable for these personality traits and where he/she can be helpful and lifesaving.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations